THE EFFECTS OF SHORT/LONG-TERM ADMINISTRATION OF DUAL ANTIPLATELET THERAPY ON RESTENOSIS IN PATIENTS WITH CAROTID ARTERY STENTING - İsmail Karluka; Hasan Bilen Onan; Erol Akgül; Erol Hüseyin Aksungur (MNJ (Malang Neurology Journal), 2023)
Background: There is no consensus on the duration of dual antiaggregant therapy after carotid stenting. This study aimed to evaluate the early contribution of dual antiaggregant therapy for three or six months to stent restenosis. Objective: This study aimed to identify the correlation between stent restenosis and the duration of dual antiplatelet therapy (DAPT) in carotid artery stenting (CAS) subjects by retrospectively scanning a CAS procedure dataset. Methods: Patients who underwent a CAS procedure received dual DAPT (acetylsalicylic acid (ASA) + clopidogrel) were recruited for this study. The first group was the patients who received dual antiaggregants for three months, and the second group was the patients who received dual antiaggregants for six months. Patients' demographic characteristics, comorbidities, and radiological results were reviewed. Follow-up activities for the following six months were assessed for stent status, complications, and new ischemic lesions. Results: A total of 65 patients received ASA (acetylsalicylic acid) + clopidogrel for six months, while the remaining 118 patients were treated for three months. The restenosis rates were not significantly different between the two groups. The complication and adverse event frequencies were also similar. Conclusion: This study revealed that the efficacy of 3-month and 6-month DAPT is similar regarding the restenosis frequency, and there are no significant differences in complication frequency.